THE EFFECT OF BLACK CUMIN (NIGELLA SATIVA L.) ON THE IMMUNE SYSTEM FOR ORAL HEALTH - Dewi, Komang Krisna; Yuditha, Solva; Kusparmanto, Lukas; Purwoko, Winda Asha (Moestopo International Review on Social, Humanities, and Sciences, 2024)
The immune system is a system that is able to protect the body from microorganisms that cause disease. This system can limit microbial colonization in the oral cavity and prevent the penetration of harmful substances. The immune system is related to health problems in the oral cavity. Black cumin (Nigella sativa L.) has the main active component, namely thymoquinone. Thymoquinone has an immunomodulatory, anti-inflammatory, analgesic, and antioxidant effect that shows an important role in oral disease management and also in oral health. Research shows that the substance thymoquinone in black cumin has an effect on increasing the immune system in the oral cavity. The research analyzed was research on the effect of black cumin on the immune system for oral health. The use of black cumin containing thymoquinone is effective for increasing the immune system in the oral cavity, if used at a concentration of 0.1%-0.2% and applied directly to the area that is experiencing inflammation. So it can be concluded that black cumin has an effect on increasing the immune system in the oral cavity.